2003
DOI: 10.1373/49.8.1337
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Amino-Terminal Fragment of Pro-Brain Natriuretic Peptide in Plasma for the Evaluation of Cardiac Dysfunction in Elderly Patients in Primary Health Care

Abstract: Background:The aims of this study were to measure the N-terminal fragment of pro-brain natriuretic peptide (proBNP) in plasma in medical conditions commonly found in primary care and to evaluate the utility of these measurements in identifying impaired cardiac function in elderly patients with symptoms associated with heart failure. Methods: We studied 415 patients (221 men and 194 women; mean age, 72 years) who had contacted a primary healthcare center for dyspnea, fatigue, and/or peripheral edema. One cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…However, from recent studies, the consequence of such a gene deletion produces at least two different features of gene arrangement. One of them presents a -C4A-CYP21P/CYP21-TNXB gene array, which produces four kinds of chimeric CYP21P/CYP21 genes (1, 13 ), whereas the other presents a -C4A-CYP21P-TNXA/TNXB array, which contains two kinds of chimeric TNXA/TNXB genes (2,4 ).…”
Section: Use Of Pcr-based Amplification Analysis As a Substimentioning
confidence: 99%
See 2 more Smart Citations
“…However, from recent studies, the consequence of such a gene deletion produces at least two different features of gene arrangement. One of them presents a -C4A-CYP21P/CYP21-TNXB gene array, which produces four kinds of chimeric CYP21P/CYP21 genes (1, 13 ), whereas the other presents a -C4A-CYP21P-TNXA/TNXB array, which contains two kinds of chimeric TNXA/TNXB genes (2,4 ).…”
Section: Use Of Pcr-based Amplification Analysis As a Substimentioning
confidence: 99%
“…On ventricular myocyte stretch, preproBNP is enzymatically cleaved to proBNP and released in the form of the hormonally active BNP and the inactive N-terminal proBNP (NT-proBNP). Both BNP and NT-proBNP have been shown to reflect heart failure severity (1 ), but studies on their sensitivity and specificity for different degrees of heart failure produced conflicting results (3)(4)(5)(6). Both BNP and NT-proBNP can be used for the diagnosis of heart failure, but there are important differences between the two tests, particularly regarding influence of age and renal function (1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed among patients with different stages of impaired renal function have shown an increase of natriuretic peptide concentration with declining glomerular filtration rate [12], especially relevant for the amino-terminal fragment of pro-BNP (NT-proBNP), which is largely eliminated by glomerular filtration only [13]. However, high levels of natriuretic peptides in patients with CKD do not simply reflect the reduced clearance of the peptide; rather, they largely reflect a true-positive finding, identifying the presence of heart disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…
In patients with ST elevation myocardial infarction (STEMI) NT-pro brain natriuretic peptide (NT-pro BNP) [1,2] and estimated glomerular filtration rate (eGFR) [3] were associated with increased risk of mortality.Previous studies examined the association between renal function and NT-pro BNP, with apparently discrepant results [4][5][6][7]. In patients undergoing non vascular surgery [8] the discriminative value of NT-pro BNP was most pronounced in patients with GFR N90 ml/min/1.73 m2 and had no prognostic value in patients with GFR b30 ml/min/1.73 m2.

No data are so far available on this topic in STEMI patients.

…”
mentioning
confidence: 99%